2002
DOI: 10.1086/338400
|View full text |Cite
|
Sign up to set email alerts
|

Response to Lamivudine-Zidovudine plus Abacavir Twice Daily in Antiretroviral-Naive, Incarcerated Patients with HIV Infection Taking Directly Observed Treatment

Abstract: Prison inmates with human immunodeficiency virus (HIV) infection can be difficult to treat because of the complexity and intrusiveness of many combination antiretroviral therapy regimens. NZTA4007, a 24-week open-label, single-arm clinical trial involving 108 antiretroviral therapy-naive, incarcerated, HIV-infected persons, was conducted to evaluate a compact regimen (4 tablets per day) consisting of 1 lamivudine-zidovudine (150 mg/300 mg) combination tablet (COM) and one 300-mg abacavir tablet administered tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 9 publications
(14 reference statements)
1
30
0
1
Order By: Relevance
“…For example, the few studies on adherence to ART in prison settings evaluated stavudine, lamivudine, zidovudine, ritonavir and saquinavir, the triple combination of zidovudine, lamivudine, and abacavir (in fixeddose formulation or not), or unspecified combinations of the various classes. 24,43,44,56 Therefore, there is clearly the need for more recent studies on HIV+ inmates who are receiving current standard-of-care antiretroviral combinations.…”
Section: Updates On Antiretroviral Treatment In Correctional Facilitiesmentioning
confidence: 99%
“…For example, the few studies on adherence to ART in prison settings evaluated stavudine, lamivudine, zidovudine, ritonavir and saquinavir, the triple combination of zidovudine, lamivudine, and abacavir (in fixeddose formulation or not), or unspecified combinations of the various classes. 24,43,44,56 Therefore, there is clearly the need for more recent studies on HIV+ inmates who are receiving current standard-of-care antiretroviral combinations.…”
Section: Updates On Antiretroviral Treatment In Correctional Facilitiesmentioning
confidence: 99%
“…Although most inmates are already infected prior to arriving at prison, intraprison transmission may occur via tattooing, injection drug use, and sex. 4 A number of correctional systems have instituted routine HIV testing, and the administration of antiretroviral therapy under direct observation maximizes adherence in these settings. This widespread availability of HAART in the prison system has been responsible for the decrease in AIDS mortality, where the rate declined from 1,010/ 100,000 in 1995 to 20/100,000 in 1999.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] The results of our study are also similar to those obtained in correctional settings and noncorrectional settings with mandatory directly observed therapy (DOT) for HAART. [37][38][39] One recent study compared patients enrolled in clinical trials who received directly observed HIV therapy in a correctional setting to those in trials in community settings. 40 Results of this study showed that 80% of patients receiving DOT achieved a nondetectable viral load compared to 50% in the selected community-derived sample.…”
Section: Discussionmentioning
confidence: 99%
“…Twice-daily therapies in incarcerated persons have even improved adherence and improved clinical outcomes, with improved HIV-1 viral load and CD4 lymphocyte counts. 37 True DOT will not likely be accomplished until once-daily regimens are truly available. 53 Approved once-a-day antiretrovirals now include didanosine, lamivudine, tenofovir, efavirenz, and the combination of amprenavir with low-dose ritonavir.…”
Section: Discussionmentioning
confidence: 99%